The Impact of Social Support on Mental Health Outcomes in Aging Populations - Priya Sharma; Arjun Singh; Neha Iyer (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study explores the role of social support in shaping mental health outcomes among aging populations. Through a survey of older adults, the research examines how family, peer, and community support influence depression, anxiety, and life satisfaction. The findings suggest that strong social networks significantly improve mental health outcomes, emphasizing the importance of social support in promoting well-being in older adults.